(3eMGSHI GdHJQhd (B/s - (3YHO GdhgGH, GHQGgje Wgs ((3GdefUhQI(B: s (3GdecJHI GdYUQjI ddfTQ hGdJhRjY(B, s, 2006)
(3UfGYI GdHJQhd hGdeMGSHI Yf GfJGL GdHJQhd, GdJfXje GdeMGSHj aj eQGMd GfJGL GdHJQhd, GdJfXje GdeMGSHj dCge GdeTcdGJ GdeMGSHjI hGdGJaGbjGJ GdHJQhdjI hfJGFL GdfTGW aj efTBJ GdHJQhd, GdfXGe GdeMGSHj dbjGS fJGFL fTGW efTBJ fGbdGJ GdHJQhd heYGdLI BKGQ JbdHGJ GdWdH YdjgGs
(3HjHdjhZQGajG(B: (3U(B.331s
Keywords: (3GdHJQhd(B- (3GbJUGOjGJ s; (3GdeMGSHIs; (3HJQhd(B-(3fbds